Incorporating Virtually Immersive Environments as a Collaborative Medium for Virtual Teaming - Charles J. Lesko, Jr.; Christine R. Russell (Journal of Education and Learning (EduLearn), 2012)
Virtually immersive environments incorporate the use of various computer modelling and simulation techniques enabling geographically dispersed virtual project teams to interact within an artificially projected three-dimensional space online. This study focused on adoption of virtually immersive technologies as a collaborative media to support virtual teaming of both graduate and undergraduate-level project management students. The data and information from this study has implications for educators using virtually immersive environments in the classroom. In this study, we specifically evaluated two key components in this paper: 1) students’ level of trust and; 2) students’ willingness to use the technology, along with their belief about the virtual environment’s ability to extend and improve knowledge sharing in their team work environment. We learned that while students did find the environment a positive add on for working collaboratively, there were students who were neither more nor less likely to use the technology for future collaborative ventures. Most of the students who were not very positive about the environment were “fence sitters” likely indicating needs related to additional training to improve communication skills. Finally, based on the full study results we have provided basic recommendations designed to support team trust building in the system along with interpersonal trust building to facilitate knowledge transfer and better strategic us of the technology.